2023
DOI: 10.1126/sciadv.ade7702
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and kinetics of the human immune cell response associated with severe dengue progression by single-cell proteomics

Abstract: Approximately 5 million dengue virus–infected patients progress to a potentially life-threatening severe dengue (SD) infection annually. To identify the immune features and temporal dynamics underlying SD progression, we performed deep immune profiling by mass cytometry of PBMCs collected longitudinally from SD progressors (SDp) and uncomplicated dengue (D) patients. While D is characterized by early activation of innate immune responses, in SDp there is rapid expansion and activation of IgG-secreting plasma c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…However, a recent study showed increased gene expression of FOXP3 in DHF compared to DF patients ( 34 ). Interestingly, the frequency of Tregs was increased in acute dengue-infected patients who progressed to severe dengue compared to patients who did not develop severe complications ( 37 , 38 ). Along the same line, in this study, we found that Tregs from severe dengue patients seemed to proliferate more compared to Tregs from classical DF patients, even though our results did not reach significance.…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent study showed increased gene expression of FOXP3 in DHF compared to DF patients ( 34 ). Interestingly, the frequency of Tregs was increased in acute dengue-infected patients who progressed to severe dengue compared to patients who did not develop severe complications ( 37 , 38 ). Along the same line, in this study, we found that Tregs from severe dengue patients seemed to proliferate more compared to Tregs from classical DF patients, even though our results did not reach significance.…”
Section: Discussionmentioning
confidence: 98%
“…Batch correction was then applied using a common control sample as previously described. 78 Fcs files were combined and individual protein channels were arcsinh-transformed with a cofactor of 5 and scaled to the 99.9 th percentile. Individual tetramer + gates were drawn by batch and class I HLA-type to identify antigen-specific CD8 + cells.…”
Section: Methodsmentioning
confidence: 99%
“…A supervised hierarchical clustering approach was employed, as previously described. 78 , 84 Cells were overclustered by FlowSOM 85 using all markers as input and clusters were manually annotated as T cells or non-T cells based on expression of CD3. Neoplastic T cell clusters were annotated based on expression of KIR3DL2, 19 absence of CD8, absence of TCRγδ, and a high proportion of cells belong to SS subjects (>93%).…”
Section: Methodsmentioning
confidence: 99%
“…Batch correction was performed utilizing a common bone marrow sample included with each batch as previously described 81 . For each protein channel, the median expression value was determined for all common samples.…”
Section: Methodsmentioning
confidence: 99%